Captive breeding and induced fertilization of Malaysian horseshoe crab (Tachypleus gigas) for sea ranching and future artificial sanctuary - John, Akbar; Chowdhury, Ahmed Jalal Khan; Yunus, Kamaruzzaman; Mohamed, Rozihan; Kassim, Zaleha (International Islamic University Malaysia, 2018)
Horseshoe crabs are the only extant Xiphosurans experiencing serious threats in terms of their nesting and spawning ground habitat degradation, over exploitation for biomedical bleeding practices and uncontrolled harvesting of their wild population for local delicacy. Hence, the current project was aimed to establish the captive breeding condition with three objectives including 1. To determine the spawning success in captivity, 2. To determine the invitro fertilization success and 3. To evaluate hatching rate of fertilized eggs to 4th instar [projected 8th instar] for sea ranching program. Results indicated that different texture and particle size of sand substrate have significant impact on number of eggs released by the female crabs in Invitro. Effect of Captive Breeding on the Amebocyte Cell Viability in Malaysian Horseshoe Crab (Tachypleus Gigas) have shown profound negative effect of captive breeding on the amebocyte viability, morphology, sperm viability and density in adult horseshoe crabs. Effect of differential feed on the molting success and survival of horseshoe crab trilobite (Tachypleus gigas) indicated that microalgae Isochrysis with the concentration of 7.5million cells/lit can be used to induce faster molting in T. gigas instar stages. Successful invitro fertilization can be achieved in captive condition with high percentage (>95%) of fertilization success.